PEMAKNAAN PESERTA DIDIK TERHADAP PILAR MENGHORMATI DALAM PROGRAM PENDIDIKAN BUDI PEKERTI BERBANTUAN KERTAS AMATAN DI SMK WIJAYA PUTRA SURABAYA - Adinda Zanata Zahra; Prof. Dr. Warsono, M.S. (Universitas Negeri Surabaya (Unesa), 2026)
This study aims to understand students’ meaning-making of the respect pillar in the Character Education Program assisted by observation sheets at SMK Wijaya Putra Surabaya, as well as to identify supporting and inhibiting factors in fostering respectful attitudes. This research employed a descriptive qualitative approach, with data collected through in-depth interviews, observations, and documentation involving students, homeroom teachers, and the PBP program management team. The findings indicate that students interpret the respect pillar as obedience to school rules, politeness in social interactions, and the ability to exercise self-control. However, such interpretations remain at a normative and administrative level and have not been fully internalized as moral awareness. From the perspective of Thomas Lickona’s character education framework, the development of moral knowing, moral feeling, and moral action has not progressed in a balanced manner, as students’ motivation is still dominated by external factors such as fear of consequences and school evaluation. Observation sheets function as reflective instruments with the potential to foster students’ self-awareness, although in practice they are often perceived as tools of behavioral control. Supporting factors in fostering respect include consistency in value habituation, a humanistic approach adopted by teachers and homeroom teachers, parental support, and a structured observation system, while inhibiting factors include limited internal awareness, peer group influence, masculine practice culture, and inconsistency in rule enforcement.